Impact of hydration status on electromyography and ratings of perceived exertion during the vertical jump - Donahue, P. T.; Wilson, S. J.; Williams, C. C.; Valliant, M.; Garner, J. C. (International Journal of Kinesiology & Sports Science, 2019)
Background: The vertical jumping task is commonly used to assess lower-body power output in athletic populations, in addition to being commonly used to during investigations of hydration and anaerobic performance. Changes in neuromuscular function during a hypohydrated state have been proposed as a potential mechanism to decreases in anaerobic performance. Objectives: The primary purpose of this investigation was to examine the impact of hydration state on electromyography during the vertical jumping task. Methods: Twenty recreationally trained males were tested in three hydration conditions (hypohydrated, euhydrated, and control). Testing included maximal voluntary contractions of the vastus lateralis, vastus medialis, semitendinosus and medial gastrocnemius. Participants performed three maximal countermovement and squat jumps respectively for a total of six jumps in each condition. Both mean muscle activity and percentage of maximal voluntary contraction were calculated across the propulsive phase of each jump. Additionally, measures of RPE and the use of a mood rating scale were used as subjective measures. Results: No differences were seen in mean muscle activity and percentage of MVC in either of the jumping conditions (p > 0.05). Significant differences were seen with higher ratings of perceived exertion as well as lower levels of mood ratings after the hypohydrated condition (p = 0.02 and p = 0.048 respectively). Conclusions: Decrements seen in vertical jump performance during a hypohydrated state appear to be caused from changes other than neuromuscular function and muscle activity. Differences in subjective measures may provide insight into changes in motivational levels and potentially impacting performance.